Growth and mineral nutrition of banana seedlings cv. Grand Naine inoculated with arbuscular mycorrhizal fungi - Fernando da Rui, Ricardo; Antonio Schiavo, Jolimar; Correa Santos, Silvia; Reis Pinheiro Lourente, Elaine; Makoto Kusano, Daniel; Rezende Ferreira, Kleiton (Comunicata Scientiae, 2022)
This study aimed to verify the influence of FMAs on the levels of macro and micronutrients, and growth of micropropagated banana seedlings submitted to doses of P. The experimental design adopted was randomized blocks, in a 5 x 5 factorial arrangement, with factors inoculation with AMFs (G. clarum, G. margarita, G. albida and C. etunicatum and the control without AMF) and P doses (0, 50, 100, 200 and 400 mg kg-1). The association of different species of FMAs can favor the growth of banana seedlings, with greater nutrition. The application of P doses provided greater growth of the micropropagated banana seedlings, regardless of inoculation with AMF. Seedling production associated with G. margarita can favor the growth of plants submitted to low doses of P applied to the soil. The interaction of G. clarum with Musa spp. seedling production does not seem to favor plant growth. Mycorrhizal colonization together with phosphate fertilization contributed to the quality of banana seedlings. The inoculation with C. etunicatum favored the increase of K contents in the aerial part of the plants. The increase in P doses decreased the levels of N and S in all treatments. It caused a reduction in the leaf contents of Mn, B and Fe. The doses of P did not interfere in the leaf contents of Cu and Zn. The FMAs favored the levels of Cu, Zn, Mn and B in banana leaves; favored the increments of Cu, Fe, Zn and Mn contents in banana seedlings, varying with the doses of P.